Composite models for compression moulded long regenerated cellulose fibre-reinforced brittle polylactide (PLA). (8th September 2017) - Graupner, Nina; Ziegmann, Gerhard; Müssig, Jörg
Abstract: The present study shows a new approach for the prediction of tensile strength values of compression moulded long cellulose fibre-reinforced brittle polylactide (PLA) composites. For this approach regenerated cellulose fibres (lyocell) of variable fineness were used as reinforcement. Composites with different fibre loadings (17, 26 and 36 vol-%) and mean fibre orientation angles ranging between ± 20 and ± 65° were manufactured. Some published models were applied to the mechanical properties of our composites. While the rule of mixture as well as the Kelly-Tyson model lead to a clear overestimation of the strength values, the model of Taha & El-Sabbagh et al. (developed for injection moulded composites) leads to a clear underestimation. On the basis of the Kelly-Tyson-model expanded with Taha & El-Sabbagh et al.'s agglomeration factor and the use of the fibre stress at the point of elongation at break of the composite a new model was created for compression moulded regenerated cellulose fibre-reinforced composites. Overall, 19 different composites were investigated. 13 of them show a deviation from the model data to the measured tensile strength of < ± 10%, 4 of them between - 10% and −15% and only 2 of them have shown a deviation of −16 and −18%, respectively.